Efektivitas Alokasi Dana Desa dalam Meningkatkan Industri Kecil Menengah Masyarakat Desa - Ina Mutmainah; Azharul Faizin (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The increase of the village fund allocation should be represented by the betterment of public services, village economic growth, and social welfare. The present study portrays how the village funds are administered to encourage small and medium enterprises (SMEs) existing in Indonesian villages. Study findings expose that the village funds were allocated in the economic sector demonstrated by the provision of shopping centers for various SMEs products in the village setting. The village funds were also optimized to strengthen the presence of the SMEs through the pivotal role of village-owned enterprises (BUMDes) and the villagers’ entrepreneurship. This study also depicts that empowering small and medium-scale enterprises could be manifested by organizing training to support the growth of the SMEs and enhance soft skills-mediated human resources.